İbnü’l Cezeri ve Camiu’l Esanid adlı eseri - Işık, İsmail (My University, 2011)
Tez Türü ve Tarihi: stanbul, 2011 ÖZET Bu çalışma İbnü’l Cezerî’nin ‘Câmiu’l Esânîd’ adlı eserini inceleme amaçlıdır. Cezerî bu eseri yazmakla neyi amaçlamıştır hangi meseleleri vurgulamak istemiştir bunu anlamaya yönelik bir çalışmadır. ‘İbnü’l Cezeri ve Câmiu’l Esânîd Adlı Eseri’ başlığı altında yapılan bu çalışma giriş ve iki ana bölümden oluşmaktadır. kısmında hayatı, ailesi, hocaları, talebeleri ve ilmi seyahatleri; ikinci kısmında ise eserleri incelenmeye çalışılmıştır. İkinci bölümün ilk kısmında isnâd konusu incelenmeye çalışılmış, ikinci kısmında ise eserle ilgili bilgiler verilmeye çalışılmıştır. Son olarak da eserin edisyon kritiği yapılmaya çalışılmıştır. Bu çalışmada, Cezerî’nin bu eserinde kendi hayatını ve özellikle hocalarını zikretmeye çalıştığını bununla birlikte isnâd sistemine de ne kadar değer verdiğini görmüş oluyoruz. Cezerî, Câmiu’l Esânîd, isnâd Degree Awarded and Date: Master thesis, Istanbul, 2011

This thesis is the outcome of the struggle for examining in detail the study entitled ‘Jamiu’l Asanid’ written by Ibn al-Jazari. Besides, the purpose of al-Jazari to write this book and which subjects he underlines are discussed in this study. This thesis conducted under the title ‘Ibn al-Jazari and His Work entitled Jamiu’l Asanid’ composes of an introduction and two main chapters. In the beginning of the first chapter, Jazari’s life, family, teachers, students, travels to get information and, in the second part of the chapter, his works are reviewed. The second chapter initially tries to examine isnad and, the information related to the book is given in the last part of the chapter. Finally, the thesis tries to critically analyse the book considering its points need to be clarified. Consequently, al-Jazari’s this book can be seen as a type of autobiography since he particularly informs about his own life and works besides referring to his teachers. In addition to this, he displays the significance he gives to the system of isnad in his book. Key words: Ibn al-Jazari, Jamiu’l Asanid, isnad
Keywords: İslam Dini; Tefsir